Praktik Tata Kelola Keuangan Pesantren Salafiyah: Sebuah Studi Etnografi - Ahmad Nurkhin; Abdul Rohman; Tri Jatmiko Wahyu Prabowo (Jurnal Sosial Humaniora, 2026)
Pondok pesantren or pesantren (Islamic boarding schools) are unique Islamic educational institutions that have actively and significantly contributed to various aspects of Indonesian society. Law No. 18 of 2019 concerning Pesantren emphasizes that pesantren are expected to be well-managed, including in their finances. This paper aims to uncover the financial governance practices of pesantren salafiyah. A qualitative research design with an ethnographic approach was conducted at Pondok Pesantren Assalafy Al Asror, a recognized and well-developed Salafiyah Islamic boarding school in Semarang. Participant observation, in-depth interviews, and documentation were applied to obtain data from kiai, nyai, administrators, alumni, and other relevant parties. Data analysis techniques were carried out through qualitative research stages. The results of the study indicate that the financial governance of the Pondok Pesantren Al Asror has been running through simple recording and reporting, simple supervision, and contributions from internal and external parties. VA technology has been implemented to strengthen revenue accountability, enabling tactical policymaking. Other results indicate that Pesantren Al Asror has not implemented Islamic boarding school accounting or institutions without public accountability, such as ISAK 35 and PAP 2024.